Study of chemical changes and antioxidant activity variation induced by gamma-irradiation on wild mushrooms: comparative study through principal component analysis - Fernandes, Ângela (2013)
Mushrooms are especially sensitive to senescence, browning, water loss and microbial attack. Furthermore, wild species are characterized for their seasonality, demanding the development of suitable preservation technology. Gamma-irradiation was previously tested in wild Lactarius deliciosus, being verified that its application up to 1 kGy did not imply significant changes in chemical parameters. Herein, the effects of higher gamma-irradiation doses, typically used in natural food matrices like fruits or vegetables, were assessed in Boletus edulis Bull.: Fr. and Hydnum repandum L.: Fr. by checking for changes in nutritional parameters, free sugars, tocopherols, fatty acids, organic acids and antioxidant activity indicators. To have representative samples, the used carpophores were collected in different maturity stages, using the same number of specimens for each stage and also for each mushroom species. The specific effects of each tested irradiation were evaluated in an integrated manner through principal component analysis. The correspondent biplots indicate that differences caused by gamma-irradiation are enough to separate irradiated and non-irradiated samples of both mushrooms. Nevertheless, nutritional profiles were not affected in high extension, indicating that gamma-irradiation, up to the doses used in this work, might represent a useful mushroom conservation technology.